Legionellosis prevention in building water and HVAC systems : a practical guide for design, operation and maintenance to minimize the risk - La Mura, Sergio; Joppolo, Cesare Maria; Piterà, Luca Alberto Piterà; Angermann, Jean Pierre; Izard, Mark (REHVA, 2013)
This Guidebook is a practical guide for design, operation and maintenance to minimize the risk of legionellosis in building water and HVAC systmes. It is devided into several themes such as: Air conditioning of the air (by water - humidification), Production of hot water for washing (fundamentally but not only hot water for washing) and Evaporative cooling tower.
Keywords: Heating -- Equipment and supplies -- Design and construction.; Ventilation -- Equipment and supplies -- Design and construction.; Air conditioning -- Equipment and supplies -- Design and construction.; elektronické knihy; electronic books